Analisis Pengaruh Nilai Perusahaan dan Kinerja Keuangan Terhadap Return Saham: Studi pada Perusahaan Otomotif - Setiawan, Daniel Imanuel; Dewi, Vera Intanie (Fakultas Ekonomi Universitas Andalas, 2024)
The objective of this study is to identify the influence of corporate value and financial performance on stock returns within the automotive industry sector. The study covers the period from December 2019 to December 2023, with a sample of 10 selected stocks. Panel Data Regression analysis is employed to assess these relationships. The results show that Total Asset Turnover (TATO), Debt to Asset Ratio (DER), and Return on Assets (ROA) have a significant partial effect on Stock Return (RS). In the simultaneous testing, Current Ratio (CR), TATO, DER, ROA, and Economic Value Added (EVA) are shown to collectively affect RS. This research provides insights for investors, offering recommendations to enhance investment portfolio optimization by considering these key variables.